Case Report: Anti-glomerular basement membrane disease following COVID-19 infection - Tse, Justin David; Wang, Jackson; Bhat, Adarsh; Gupta, Rajib Kumar (Frontiers in Nephrology, 2025)
Anti-glomerular basement membrane (anti-GBM) disease is a rare autoimmune disorder characterized by circulating autoantibodies targeting type IV collagen, leading to rapidly progressive glomerulonephritis. We report a case of a 44-year-old African American female with a history of hypertension who presented with acute kidney injury, hematuria, and shortness of breath. She tested positive for COVID-19 and received antiviral therapy; however, her renal function rapidly deteriorated, with serum creatinine rising from 3.4 to 10 mg/dL. Serologic testing ruled out common autoimmune conditions, but elevated CH50 levels suggested ongoing immune activation. Renal biopsy demonstrated diffuse necrotizing crescentic glomerulonephritis with linear IgG staining, consistent with anti-GBM disease. Despite aggressive therapy, including plasmapheresis, corticosteroids, and dialysis, renal recovery was not achieved. Immunosuppressive therapy was deferred in light of her active COVID-19 infection and the risk of immunosuppression-related complications. This case highlights a potential association between COVID-19 and anti-GBM disease, suggesting viral-induced endothelial injury and aberrant immune activation as possible mechanisms. Given emerging reports of autoimmune kidney diseases following COVID-19, further research is needed to clarify this relationship and guide optimal management. This is particularly important for patients who present with severe renal dysfunction in the context of an active infection.